2016
DOI: 10.1016/j.placenta.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and sex-specific differences in placental pathology

Abstract: Maternal obesity results in placental overgrowth and fetal hypoxia as manifested by normoblastemia; it is also associated with an increased incidence of CV and fetal thrombosis, both more prevalent in female placentas. We have shown for the first time that the effect of maternal obesity on placental inflammation is independent of diabetes and hypertension, but significantly affected by fetal sex. Our data also point to the intriguing possibility that CV serves to normalize placental size, and potentially fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 29 publications
2
64
5
Order By: Relevance
“…; Leon‐Garcia et al . ). In addition, maternal diet or stress has been shown to induce male‐specific placental inflammation in rodent models (Bronson & Bale ; Reynolds et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Leon‐Garcia et al . ). In addition, maternal diet or stress has been shown to induce male‐specific placental inflammation in rodent models (Bronson & Bale ; Reynolds et al .…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with previous reports from human placentas, the most interesting finding in our study is that multiple genes related to inflammation and immune response are expressed higher in males and are more induced by Dex in a male-specific manner. Importantly, substantial evidence has been accumulated to demonstrate the effect of fetal sex on placental inflammation and sex-specific differences in placental pathology, with a variety conditions such as maternal obesity, preterm delivery, PE and IUGR (Ghidini & Salafia 2005;Walker et al 2012;Leon-Garcia et al 2016). In addition, maternal diet or stress has been shown to induce male-specific placental inflammation in rodent models (Bronson & Bale 2014;Reynolds et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been shown to directly increase lipid accumulation in human trophoblasts23, therefore it may also contribute to the increased placental lipid accumulation. Other factors that may contribute to a hypoxic state include inflammation2425 and mitochondrial dysfunction26 which are observed preferentially in female placentae, while other factors such as oxidative stress27 and ER stress28 appear to be sex-independent.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, blood levels of galectin‐9, but not sPD‐L1, were significantly higher in pregnancies with male fetuses compared to females. Studies of the placenta indicated that inflammation was more common in obese mothers with female fetuses compared to male fetuses . Systemically, male fetuses induce a more inflammatory state in the maternal blood during pregnancy than females .…”
Section: Discussionmentioning
confidence: 99%